運算式 23: "y" equals 1.2 "x" plus 1.7 left brace, 2 less than "y" less than 2.8 , right bracey=1.2x+1.72<y<2.8
23
運算式 24: "y" equals 1.2 "x" plus 0.9 left brace, 1.4 less than "y" less than 2.8 , right bracey=1.2x+0.91.4<y<2.8
24
運算式 25: "y" equals negative 10 "x" plus 5.8 left brace, 0 less than "y" less than 1.4 , right bracey=−10x+5.80<y<1.4
25
運算式 26: "y" equals 1.2 left brace, 1.6 less than "x" less than 2.2 , right bracey=1.21.6<x<2.2
26
運算式 27: "y" equals 0.5 left brace, 1.4 less than "x" less than 2.1 , right bracey=0.51.4<x<2.1
27
運算式 28: "y" equals 1.6 5 left brace, 1.8 less than "x" less than 2.4 , right bracey=1.651.8<x<2.4
28
運算式 29: "y" equals 2.3 left brace, 2 less than "x" less than 2.8 , right bracey=2.32<x<2.8
29
運算式 30: "y" equals 3.2 "x" plus negative 6.1 left brace, 2.2 7 less than "x" less than 2.4 3 , right bracey=3.2x+−6.12.27<x<2.43
30
運算式 31: "y" equals 0 left brace, negative 4.1 less than "x" less than negative 3.5 , right bracey=0−4.1<x<−3.5
31
運算式 32: "y" equals 0 left brace, negative 3 less than "x" less than negative 2.4 , right bracey=0−3<x<−2.4
32
運算式 33: "y" equals 0 left brace, negative 2.1 less than "x" less than negative 1.4 , right bracey=0−2.1<x<−1.4
33
運算式 34: "y" equals 0 left brace, negative 1.1 less than "x" less than negative 0.5 , right bracey=0−1.1<x<−0.5
34
運算式 35: "y" equals 0 left brace, 0 less than "x" less than 1 , right bracey=00<x<1
35
運算式 36: "y" equals 0.4 "x" plus negative 1.2 left brace, negative 3.7 less than "x" less than 5.9 , right bracey=0.4x+−1.2−3.7<x<5.9
36
運算式 37: "y" equals 0.1 left parenthesis, "x" plus 4.2 , right parenthesis squared minus 2.7 left brace, negative 4.8 less than "x" less than negative 3.6 8 3 , right bracey=0.1x+4.22−2.7−4.8<x<−3.683
37
運算式 38: "y" equals 1.4 left parenthesis, "x" plus 4.8 , right parenthesis squared minus 2.6 7 left brace, negative 5.5 less than "x" less than negative 4.8 , right bracey=1.4x+4.82−2.67−5.5<x<−4.8
38
運算式 39: "x" equals 0.4 left parenthesis, "y" plus 1.5 , right parenthesis squared minus 5.6 left brace, negative 2 less than "y" less than negative 1 , right bracex=0.4y+1.52−5.6−2<y<−1
39
運算式 40: "x" equals 0.2 left parenthesis, "y" plus 1.7 , right parenthesis squared minus 5.6 left brace, negative 1 less than "y" less than 1.1 , right bracex=0.2y+1.72−5.6−1<y<1.1
40
運算式 41: "y" equals 0.2 5 "x" minus 0.3 left brace, 2 less than "x" less than 5.9 , right bracey=0.25x−0.32<x<5.9
41
運算式 42: "y" equals 0.2 5 "x" minus 0.3 left brace, negative 3.2 5 less than "x" less than 1.2 , right bracey=0.25x−0.3−3.25<x<1.2
42
運算式 43: "x" equals 0.3 left parenthesis, "y" plus 0.1 , right parenthesis squared minus 4.5 left brace, negative 0.5 less than "y" less than 1.0 1 2 , right bracex=0.3y+0.12−4.5−0.5<y<1.012
43
運算式 44: "y" equals 0.5 3 left parenthesis, "x" plus 3.4 , right parenthesis squared minus 1.1 left brace, negative 4.4 6 less than "x" less than negative 3.3 , right bracey=0.53x+3.42−1.1−4.46<x<−3.3